Pengaruh Kelembagaan, Pembiayaan, dan Kemandirian terhadap Kewirausahaan Petani Padi metode Hazton di Kabupaten Menpawah Kalimantan Barat - Ridha Rizki Novanda (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2020)
Menpawah Regency is the central potential for Hazton's cultivation to be developed. This must be demonstrated by the entrepreneurial spirit of farmers in their development. Therefore it is important to analyze how the influence of institutions, financing, and independence on entrepreneurship of rice farmers. The study was conducted on Hazton rice farmers. The sampling location was chosen purposively in the Hazton rice production center. The results showed that institutional, financing, and independence had a significant effect on entrepreneurship. The significance value is 0.002; 0,003; and 0.002. The value of the institutional odds ratio of 2.73 means that entrepreneurship is highly determined if the institutional conditions are 2.73 times. The value of the odds ratio of financing of 1.85 means that entrepreneurship is very determined by institutional conditions as much as 1.85 times. And the value of the odds ratio of independence of 2.68 means that entrepreneurship is very determined if the independence condition is 2.68 times.